2011
DOI: 10.1121/1.3652866
|View full text |Cite
|
Sign up to set email alerts
|

Spectral loudness summation of nonsimultaneous tone pulses

Abstract: The level of broadband signals is usually lower than that of equally loud narrow-band signals. This effect, referred to as spectral loudness summation, is commonly measured for broadband signals where all frequency components are presented simultaneously. The present study investigated to what extent spectral loudness summation also occurs for nonsimultaneously presented frequency components. Spectral loudness summation was measured in normal-hearing listeners with an adaptive forced-choice procedure for seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is unlikely that the loudness equalization of the bands or the spectral notch between adjacent bands caused the difference in the results between the present study and that of Rennies and Verhey [31]. Heeren et al [93] found larger spectral loudness summation for a sequence of short complex tones than for long complex tones with the same spectrum, similar to the duration effect of spectral loudness for noise bursts [8], [9], [91]. Thus, the effect of duration on spectral loudness summation does not require a continuous spectrum between the lowest and highest frequency components of the stimulus.…”
Section: Discussionmentioning
confidence: 49%
“…It is unlikely that the loudness equalization of the bands or the spectral notch between adjacent bands caused the difference in the results between the present study and that of Rennies and Verhey [31]. Heeren et al [93] found larger spectral loudness summation for a sequence of short complex tones than for long complex tones with the same spectrum, similar to the duration effect of spectral loudness for noise bursts [8], [9], [91]. Thus, the effect of duration on spectral loudness summation does not require a continuous spectrum between the lowest and highest frequency components of the stimulus.…”
Section: Discussionmentioning
confidence: 49%
“…Chalupper and Fastl (2002) used the same release and attack time constant in the integration stage. However, this model also has a slight asymmetry due to a simulated forward masking effect included in the model (Heeren et al, 2011). Simulations by Pedersen (2006) and our own unpublished simulations indicate that these dynamic models hardly predict the primacy effect observed in the studies mentioned above.…”
Section: Primacy Effect In the Light Of Current Loudness Modelsmentioning
confidence: 82%
“…The same adaptive two-alternative forced-choice procedure as described in [11] wasu sed to measure leveld ifferences at equal loudness for as ubset of the stimuli described above.Subjects heard twosounds (a reference and at est signal)s eparated by 500 ms of silence. Subjects looked at av isual display comprising twob uttons corresponding to the twosounds, and the corresponding button wasv isually highlighted during the presentation of test and reference stimulus, respectively.T he duration of the interval wass et to 2.46 s, i.e., the duration of the longest stimulus.…”
Section: Loudness Matchingmentioning
confidence: 99%
“…In addition, loudness also depends on signal duration (e.g., [7,8,9]), which is known as temporal integration of loudness. Recent studies have reported an interaction of these twoeffects in that spectral loudness summation is generally larger for short than for long stimuli [6,10,11]. In the studies mentioned above,t he basic effects of signal parameters on loudness have mostly been investigated using rather artificial stimuli (e.g., bursts of tones or noise).…”
Section: Introductionmentioning
confidence: 97%